Reduced death rates from cyclones in Bangladesh: what more needs to be done? - Ubydul Haque; Masahiro Hashizume; Korine N Kolivras; Hans J Overgaard; Bivash Das; Taro Yamamoto
Tropical storms, such as cyclones, hurricanes and typhoons, present major threats to coastal communities. Around two million people worldwide have died and millions have been injured over the past two centuries as a result of tropical storms. Bangladesh is especially vulnerable to tropical cyclones, with around 718 000 deaths from them in the past 50 years. However, cyclone-related mortality in Bangladesh has declined by more than 100-fold over the past 40 years, from 500 000 deaths in 1970 to 4234 in 2007. The main factors responsible for these reduced fatalities and injuries are improved defensive measures, including early warning systems, cyclone shelters, evacuation plans, coastal embankments, reforestation schemes and increased awareness and communication. Although warning systems have been improved, evacuation before a cyclone remains a challenge, with major problems caused by illiteracy, lack of awareness and poor communication. Despite the potential risks of climate change and tropical storms, little empirical knowledge exists on how to develop effective strategies to reduce or mitigate the effects of cyclones. This paper summarizes the most recent data and outlines the strategy adopted in Bangladesh. It offers guidance on how similar strategies can be adopted by other countries vulnerable to tropical storms. Further research is needed to enable countries to limit the risks that cyclones present to public health.